Integration of Field Leadership and Battalion Strategy in Enhancing Soldiers’ Mission Success in High-Risk Areas - Jeffy Satriansyah; Sunarko Sunarko; Rudi Lazuardi (International Journal Labs, 2026)
Sarmi Regency, Papua, was selected as the research locus due to its challenging geographical conditions, limited logistical access, and asymmetric security threat dynamics, which require adaptive leadership effectiveness and operational strategy. This study aims to analyze the influence of field leadership style and battalion strategy on the success of soldiers’ missions in security operations conducted in high-risk areas. The study employed a quantitative approach with an explanatory research design to examine the causal relationship between field leadership style (X1) and battalion strategy(X2) on mission success (Y), both partially and simultaneously. The research population consisted of approximately 500 soldiers, with a sample of 222 respondents determined using the Slovin formula and a purposive sampling technique. Data were collected through a five-point Likert-scale questionnaire that met validity and reliability requirements. Data analysis was conducted using simple linear regression and multiple linear regression, accompanied by t-tests, F-tests, and the coefficient of determination (R²). The results indicate that field leadership style has a positive and significant effect on mission success, as does battalion strategy. Simultaneously, both variables explain 56.3% of the variance in mission success. These findings confirm that mission success in high-risk areas is the result of the integration of adaptive field leadership and structured, contextual battalion strategy.